POLA REKRUTMEN POLITIK BERDASARKAN IDEOLOGI PARTAI POLITIK DALAM SISTEM KETATANEGARAAN INDONESIA: - - Suhaimi, Else (Universitas Islam Negeri Raden Fatah Palembang, 2018)
Political recruitment is a process of selecting and selecting a person or several members of the community to occupy and exercise certain political roles as cadres of political parties, legislators, as president and vice president and as regional head. In the Indonesian state system, this political recruitment is left to political parties. The rise of political parties as a result of freedom of association and assembly on the one hand is a reflection of democracy but on the other hand the large number of political parties will give rise to increasingly tight competition between political parties. The increasing competition makes political actors easily trapped in political pragmatism. Political pragmatism as a short-term orientation of political actors to win political competition is power. Power as the ultimate goal of the political competition. Political pragmatism has had a significant impact on the formation of pragmatic recruitment patterns. The pattern of pragmatic recruitment has spawned many problems, especially issues related to the quality of recruitment results. One of them is that many of the political elites are facing legal problems such as corruption and so on. Under these conditions emerged initiatives to present a systematic and structured pattern of political recruitment. One of the indications is that political recruitment is based on the ideology of political parties. The ideology of a political party is broadly divided into recruitment based on Islamic ideology (religion) and other ideologies such as nationalism. the closer the party ideology to the party recruitment pattern will result in quality recruitment and visionary cadres. on the contrary, the further distance the party ideology with the party recruitment pattern will result in a pragmatic recruitment. The results of recruitment have a close relationship with the quality of products produced, especially product legislation. Kata Kunci : pola rekrutmen, partai politik, sistem ketatanegaraan